Compete to play: trade-off with social contact in long-tailed macaques (Macaca fascicularis). - Sébastien Ballesta; Gilles Reymond; Mathieu Pozzobon; Jean-René Duhamel (PLoS ONE, 2014)
Many animal species engage in various forms of solitary object play, but this activity seems to be of particular importance in primates. If playing objects constitute a valuable resource, and access to such objects is limited, a competitive context may arise. We inserted a unique toy within a mini-colony of long-tailed macaque (Macaca fascicularis) and compared their behaviors to sessions without playing object. An automatic color-based 3D video device was used to track the positions of each animal and the toy, and this data was categorized into 5 exclusive behaviors (resting, locomotion, foraging, social contact and object play). As expected, the delay to first access to the object reflected the hierarchy of the colony, indicating that a competition took place to own this unique resource of entertainment. In addition, we found that the amount of object play was not correlated with social or foraging behavior, suggesting independent motivational mechanisms. Conversely, object playing time was negatively correlated with idling time, thus indicating its relation to pastime activities. Interestingly, the amount of social contacts in the group was significantly reduced by the heightened competitive context, suggesting that competitors are more likely to be perceived as potential threat requiring caution, as shown in humans. Experimental manipulation of competitive contexts in primates reveals common mental processes involved in social judgment, and shows that access to valuable resources can be a sufficient cause for variations in group cohesion.